Introducer Witness On Notary’s Deed Establishment: Forgotten Role in Indonesia Notarial Law - Monica Firda Nurjannah; Sri Budi Purwaningsih; Mochammad Tanzil Multazam; Emy Rosnawati (Rechtsidee, 2018)
In Law Number 2 Year 2014 regarding the Amendment of UUJN (UUJN-P) Juncto Law Number 30 of 2004 concerning Notary (UUJN) mentioned that was possible if there is a sign witness or an introducer witness. However, in Notary Law is not yet be regulated explicitly about legal protection for introducer witness who signed in a notarial deed. The purpose of this study was to know the legal protection for the introducer witness who signed in a notarial deed. The Type of research used in this research is normative, with statue approach and the results will be presented descriptively with deductive logic. The result of research shows that legal protection for introducer witness is can’t be sued because he is responsible the formal truth about people to notary only .The benefit of this research is bring information to public about legal protection for the instroducer witness.